2016
DOI: 10.20941/2414-2115.2016.02.5
|View full text |Cite
|
Sign up to set email alerts
|

Basics of Formation of Iron Borid e Coatings

Abstract: Main features of formation of iron boride layers in surface coatings on iron, its alloys, notably with chromium, and steels are discussed. Those include their microstructure, phase identity, chemical composition, sequence of occurrence, growth kinetics, and dry wear resistance. Two different kinds of layer microstructure (single-phase and twophase) are shown to exist. Boriding of iron-chromium alloys (5-30% Cr) and chromium steels (13 and 25% Cr) at 850-950ºC and reaction times up to 43200 s is found to result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…The Hf 2 Fe peaks point disordered thin clusters of tissuefree Hf-Fe bonds from the surface interlayer of pure Hf. According to the phase diagram, the Hf 2 Fe phase is most likely to form when the percentage of Hf is below 60%, which is achieved by huge abundance of boron only [33].…”
Section: Resultsmentioning
confidence: 99%
“…The Hf 2 Fe peaks point disordered thin clusters of tissuefree Hf-Fe bonds from the surface interlayer of pure Hf. According to the phase diagram, the Hf 2 Fe phase is most likely to form when the percentage of Hf is below 60%, which is achieved by huge abundance of boron only [33].…”
Section: Resultsmentioning
confidence: 99%
“…In the particular case of chromium, it can form dispersed and independent chromium borides with a crystal lattice parameter very close to iron borides (iron monoboride and diiron boride) and dissolve in these phases. Due to the ability of chromium to concentrate in the outer part of the double phase (FeB–Fe 2 B) [ 59 ] the high chromium concentration in the substrate of about 13.7%, and the high chemical affinity of chromium with boron (chromium monoboride, chromium diboride, chromium tetraboride, chromium diboride, dichromium triboride, tetrachromium triboride, and pentachromium triboride) [ 25 , 60 ] coupled with the thickness at which the cobalt radiation used can penetrate ranges between 15 and 20 μm, the presence of chromium monoboride and chromium diboride phases in the X-ray analysis is explained. The identification of metal borides depends on their affinity for boron atoms and the selection of boronizing parameters and volume fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Dybkov [ 25 ] conducted a comprehensive study on forming boride coatings on different substrates using two differential equations. Samples of other steels were embedded in a boron-rich mixture containing 5% potassium tetrafluoroborate as an activator (KBF 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Fellner and Chrenkova [41], different carbon-and high-chromium ledeburitic steels were borided in a molten mixture of boron carbide and borax, and achieved very similar outcomes and explanations. In a study by Dybkov [16], steels were borided with different Cr contents and reported a significantly higher chromium content in Fe 2 B than in FeB. In addition to the fact that the Fe 2 B is first enriched by the chromium diffusion from the substrate, the isomorphism of the two phases Fe 2 B and Cr 2 B should be considered [41].…”
Section: Sem Examinations and Eds Analysismentioning
confidence: 99%
“…However, in the case of high-alloy steels, it is difficult to obtain the Fe 2 B layer solely. In this case, the thickness of FeB phase can reach 50% of the total layer thickness [15,16]. In the case of chromium steels, the chromium borides (Cr x B y ) may be present in the boride layers as precipitates [17].…”
Section: Introductionmentioning
confidence: 99%